2013
DOI: 10.1126/science.1239213
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Seismicity Rates and Operational Parameters at the Salton Sea Geothermal Field

Abstract: Geothermal power is a growing energy source; however, efforts to increase production are tempered by concern over induced earthquakes. Although increased seismicity commonly accompanies geothermal production, induced earthquake rate cannot currently be forecast on the basis of fluid injection volumes or any other operational parameters. We show that at the Salton Sea Geothermal Field, the total volume of fluid extracted or injected tracks the long-term evolution of seismicity. After correcting for the aftersho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(125 citation statements)
references
References 32 publications
4
110
0
Order By: Relevance
“…The physical connection between operational parameters such as injected volume and the seismic response can be complex. In the Salton Sea Geothermal Field, for example, the seismicity rate positively correlates with the net volume of produced fluid (extraction minus injection) rather than net injection, as would be expected if seismicity rate simply tracked pore pressure (39). This underscores the importance of geomechanical modeling for transferring understandings developed in one setting to others.…”
Section: Other Causes Of Induced Earthquakesmentioning
confidence: 86%
“…The physical connection between operational parameters such as injected volume and the seismic response can be complex. In the Salton Sea Geothermal Field, for example, the seismicity rate positively correlates with the net volume of produced fluid (extraction minus injection) rather than net injection, as would be expected if seismicity rate simply tracked pore pressure (39). This underscores the importance of geomechanical modeling for transferring understandings developed in one setting to others.…”
Section: Other Causes Of Induced Earthquakesmentioning
confidence: 86%
“…According to this, a time lag of even several months is not unexpected and it is controlled by factors such as distance of injection sites from pre-existing fault structures, hydraulic diffusivity and regional stresses (e.g. Brodsky and Lajoie 2013;Langenbruch and Zoback, 2016). In the NW The Geysers area, Johnhson et al (2016) showed that the seismicity rates during 2005-2007 indicate a 2-5 months' time lag for all depth intervals, while after 2007 there is no resolvable time lag in the shallow depth intervals (1-2 km), where most of the injection is occurring.…”
Section: Discussionmentioning
confidence: 99%
“…The most important feature of seismicity (either induced or triggered) in geothermal fields is its direct correspondence to and dependence on the operational processes, such as fluid injection or production volumes, rates and pressures (e.g. Brodsky & Lajoie 2013). Such relation has been theoretically formulated and established by the non-linear pore pressure diffusion concept (Shapiro & Dinske 2009), or alternatively, by the application of a static stress model based on the non-critical precursory accelerating seismicity theory (Mignan 2016) to induced seismicity.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers (Eberhart-Phillips and Oppenheimer, 1984;Oppenheimer, 1986;Smith and others, 2000) indicated that some seismicity near the Geysers, California, may be induced. Several researchers (Brodsky and Lajoie, 2013;Wei and others, 2015) discussed indirect relationships between fluid injection activities and the triggering of two strike-slip shocks with magnitudes larger than M5.3 near Brawley, Calif., in the Salton Trough. These areas could be considered in future assessments but were not considered here.…”
Section: Region Referencementioning
confidence: 99%
“…Coso region, California Feng and Lees (1998) The Geysers, California Eberhart-Phillips and Oppenheimer (1984), Oppenheimer (1986) Salton Trough, California Brodsky and Lajoie (2013), Wei and others (2015) Los Angeles Basin, California Hauksson and others (2015) Sleepy Hollow, Nebraska Rothe and Lui (1983) Rattlesnake Canyon, New Mexico Sanford and others (1993) Bakken Shale, Montana-North Dakota Frohlich and others (2015) Belmont/Guernsey County, Ohio Skoumal and others (2015a) Harrison County, Ohio Friberg and others (2014), Skoumal and others (2015a) Washington County, Ohio Skoumal and others (2015a) Permian Basin, Texas-New Mexico Wesson and Nicholson (1987) To generate this model, we have held discussions with many scientists and engineers from national, State, and local government agencies; industry; and academia to define data, methods, and models that are most applicable for assessing induced earthquake hazard. This model was also discussed and reviewed by our National Seismic Hazard and Risk Assessment Steering Committee, which is composed of hazard experts from across the United States.…”
Section: Region Referencementioning
confidence: 99%